Towards an Amalgamated Framework for the Green Retrofitting Process of Healthcare Facilities - Ergin, Aslıhan; Tekce, Işılay (İstanbul Üniversitesi, 2023)
Healthcare service providers have focused on the environmental effects of healthcare facilities (HFs) in recent years in order to mitigate the environmental impact of HFs, sustain the well-being of occupants and patients, and delineate the targets of the Sustainability Development Goals (SDGs), the Paris Agreement, and the 2021 United Nations Climate Change Conference (COP26) Special Report on Climate Change and Health. Because the fundamental aims of healthcare are to improve patient health and sustain the daily operations of an HF, green retrofitting practices in HFs form a crucial link between providing environmentally friendly HFs and patient health and well-being. Hence, the main objective of this paper is to propose an amalgamated green retrofitting framework for healthcare facilities by analyzing existing retrofitting methodologies and approaches. Normative refinement and frequency analyses were applied when reviewing the healthcare-specific green retrofitting methodologies and approaches for determining the dimensions and criteria to consider for the framework. Expert feedback also contributed to the framework’s improvement and modification based on the methodology’s validation step. The finalized conceptual framework is anticipated to facilitate an understanding of the fundamental considerations for green retrofitting HFs and to serve as a guide for healthcare building providers, academicians, and green building professionals.
Keywords: Architecture (Other); Mimarlık (Diğer)